The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1246/bcsj.20110225
|View full text |Cite
|
Sign up to set email alerts
|

Polymers in Ionic Liquids: Dawn of Neoteric Solvents and Innovative Materials

Abstract: In this paper, we review recent advances in the use of polymers in ionic liquids (ILs) from the view point of the "dawn of neoteric solvents and innovative materials." The first part of this paper presents a brief review of the solubility parameters of ILs, which are expected to serve as a qualitative guide for predicting polymer solubility in ILs; however, this concept cannot be used to rationalize a number of cases in which strong Coulombic interactions dominate the solubility parameters of the ILs. Thus, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 231 publications
4
144
0
Order By: Relevance
“…This was attributed to emim NTf 2 being a good solvent for PMMA chains and a poor solvent for the PS. 53 Hence, upon forming a block copolymer/IL blend, the emim NTf 2 preferentially interacts with the PMMA chains and screens the PMMA/PS interactions. This has the effect of decreasing the compatibility of the PMMA and PS chains, which increases the effective χ PS-PMMA parameter.…”
Section: Investigation Of the Effect Of Blended Emim Nt F 2 On The Bumentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to emim NTf 2 being a good solvent for PMMA chains and a poor solvent for the PS. 53 Hence, upon forming a block copolymer/IL blend, the emim NTf 2 preferentially interacts with the PMMA chains and screens the PMMA/PS interactions. This has the effect of decreasing the compatibility of the PMMA and PS chains, which increases the effective χ PS-PMMA parameter.…”
Section: Investigation Of the Effect Of Blended Emim Nt F 2 On The Bumentioning
confidence: 99%
“…Upon incorporation of 10% emim NTf 2 , only a single T g at 106°C could be observed, and this decreased slightly to 104°C for IL concentrations of 25% and 40%. Based on the solubility of PMMA in emim NTf 2 and insolubility of PS in the IL, 53 these results were attributed to the PMMA block being plasticized, and the PS block remaining essentially unaffected. In support of this, Susan et al 55 have shown that blends of PMMA homopolymer and emim NTf 2 have T g values below room temperature for similar degrees of incorporation.…”
Section: Other Factors That May Influence Applicability To Dsamentioning
confidence: 99%
“…[18] As an alternative, UCST polymers in organic solvents or in water-organic binary solvent mixtures have shown attractive properties. [42][43][44][45][46][47] Ethanol/water solvent mixtures are environmentally friendly solvents that exhibit interesting abnormal properties due to the presence of hydration shells around the ethanol molecules. [48][49][50] For instance, the presence of such hydration shells has been reported to result in solubility maxima for drug molecules in ethanol/water mixtures with certain ratios.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have also conducted fundamental studies on the compatibility and phase behavior of polymers in ILs. 32 Later, we extended out studies of Electrochemistry, 84 (9), 642-653 (2016) polymer electrolytes further to include the combination of taskspecific ILs such as protic ionic liquids (vide infra) and Li + -solvate ionic liquids. 33 The most striking differences of polymer electrolytes of ILs ("ion gels") from polyether electrolytes are the plasticizing effect of the ILs on the polymers and the decoupling of ion transport from the segmental motion of the polymer, enabling fast ion transport that is close to that of ILs themselves.…”
Section: Polymer Electrolytes Of Ils (Ion Gels)mentioning
confidence: 99%